Leisure life : myth, masculinity and modernity - Blackshaw, Tony (Routledge, 2003)
Leisure Life is a ground-breaking study of men and masculinity. Focusing on the social networks and leisure lifestyles of a particular group of working-class men - 'the lads' - Tony Blackshaw argues that traditional social collectivities such as class are being superseded. Instead, leisure life is now the central arena in which individuals assert their identities and confirm their belonging. For 'the lads', leisure time is the pivotal point in a fragmented life which not only allows them to fashion some sense of order in a world of endemic disorder but also provides opportunities for the assertion of their masculinity.The book uniquely combines 'the lads'' own raw and compelling accounts of their leisure experiences with a sophisticated interpretive analysis. In doing so, it draws on the work of major theorists such as Baudrillard, Derrida, Foucault, and especially Bauman to develop new critical insights into our understanding of the meaning of leisure.Leisure Life awakens the sociological imagination. It offers a new approach to the study of masculinity and the ethnography of leisure, making it appropriate for courses in sociology, leisure, cultural and gender studies.